A Framework to Ensure Patient Partners Have Equal and Contributing Voices Throughout the Research Program Evaluation Process. (November 2020) - Hillier, David R.; Tang, Mila; Clark, William; MacDonald, Cynthia; Connolly, Carol; Large, Chantel; King, Malcolm; Singer, Joel; Levin, Adeera; Manns, Braden; Konvalinka, Ana; Scholey, James; et al.
Purpose of program: Traditionally, peer review was a closed process conducted only by individuals working in the research field. To establish a more integrated and patient-centered approach, one of Canada's largest kidney research networks (Can-SOLVE CKD) has created a Research Operations Committee (ROC) that includes patients as key members. The ROC represents one way for achieving meaningful patient-oriented research (POR). Source of information: Can-SOLVE CKD, a network created as part of the Canadian Institutes of Health Research (CIHR) Strategy for Patient-Oriented Research (SPOR). Methods: The ROC consists of patients, physicians, scientists, Indigenous partners, experts in research methodology, and a member of Can-SOLVE CKD's operational team. On an annual basis, Can-SOLVE CKD's research teams provide the ROC with a review package, which incorporates information from patient engagement check-in calls and surveys, the project's knowledge translation plan and products, and a progress report written by the project team. The ROC evaluates the review package and provides feedback and recommendations accordingly. Key findings: The transparent nature of the process, regular feedback and review, along with an overt accountability and scoring system, has been embraced by both patients and researchers. As a result of the ROC process, the number of patient leads for each project has grown over a 3-year period and more researchers have received POR and cultural sensitivity training. Limitations: While anecdotal evidence suggests this approach is beneficial for achieving POR, formal mechanisms of evaluation are currently lacking. Implications: This ROC framework ensures patients are active contributors throughout the research process and could be adopted by other organizations to achieve a more patient-centered approach to research.